PENGUKURAN WAKTU KERJA DENGAN METODE STOP WATCH TIME STUDY - Syafril Syafar; Rahmat Hidayat; Dewi Apriyanti (Jurnal Teknik Industri Terintegrasi, 2019)
Measurement of work time with the stopwatch time study method is a measurement to observe the activities carried out repeatedly. The work measurement results can be used to obtain standard time and standard output which can later be used to carry out production planning. The purpose of this study was to determine the operating time of each unit of product worked at Pondok Neubel and to determine the standard working time of production processes at Pondok Neubel. Results of the study The total cycle time value of all activities in the neubel cottage was 2400 seconds and the normal time for each activity with a performance rating of 10 was 24000 seconds. The conclusion of this study, factors that influence the performance of workers in neubel huts are fatigue factors.